2011
DOI: 10.21273/hortsci.46.6.948
|View full text |Cite
|
Sign up to set email alerts
|

‘Bonita’ Sweetpotato

Abstract: Additional index words. vegetable breeding, disease resistance, cultivar 'Bonita' sweetpotato [Ipomoea batatas (L.) Lam.] was developed by the Louisiana Agricultural Experiment Station to provide a specialty-type white-fleshed, tan-skinned cultivar similar to 'O'Henry' but with southern root-knot nematode and soil rot resistance, superior storage root shape, and a higher dry matter content. 'Bonita' produces excellent numbers of uniform plants (sprouts) early in the production season. Days to harvest for 'Boni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The genetic basis for RKN resistance in cv. Bonita is unknown, but La Bonte et al (2011) reported cv. Bonita to be highly resistant to Mi -3 in greenhouse studies.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic basis for RKN resistance in cv. Bonita is unknown, but La Bonte et al (2011) reported cv. Bonita to be highly resistant to Mi -3 in greenhouse studies.…”
Section: Discussionmentioning
confidence: 99%
“…'NC05-198' is a rose-skinned, orange-fleshed variety being considered for release by the North Carolina Sweetpotato Breeding and Genetics Program, probably in 2016 (K. Pecota and G. Yencho, personal communication). 'Bonita' is a white-skinned, white-fleshed variety considered to be superior to 'O'Henry' (whiteflesh variety), and also has smoother root surface and a drier, sweeter flesh (La Bonte et al, 2011;North Carolina Crop Improvement Association, 2015). 'Orleans' is similar to 'Beauregard' in yield, skin color, flesh color, and sugar content but tends to have an elliptic and more consistent root shape than 'Beauregard' (La Bonte et al, 2012).…”
mentioning
confidence: 99%